Pulmonary artery‐focused contrast echocardiography with supplemental oxygen(PCESO) for echocardiographic diagnosis of anomalous origin of left coronary artery from pulmonary artery: Novel use of an old technique - Malakan Rad, Elaheh (Clin Case Rep, 2019)
Pulmonary artery‐focused agitated saline contrast echocardiography unveils tricky cases of ALCAPA by the entry of microbubbles into the left coronary artery (LCA) during systole and retrograde flow from LCA into the main pulmonary artery during diastole. Associated pulmonary hypertension, if present, augments the former flow and supplemental oxygen increases the latter.